Linking glycation and glycosylation with inflammation and mitochondrial dysfunction in Parkinson's disease - Videira, Paula A. Q. (2018)
This work was supported by Fundacao para a Ciencia e a Tecnologia (FCT), and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728).